Studi Literature Riview: Pengaruh Diksi terhadap Gaya Bahasa dalam Karya Sastra - Nur Handayani; Usiono Usiono (PT. Alahyan Publisher Sukabumi, 2025)
The role of language and language style in literary works-especially song lyrics and short stories-is the subject of this research. Language is a means of communication, and through literary works, ideas, emotions, and thoughts can be conveyed. According to Keraf's theory, word choice (diction) and language styles, such as rhetorical and figurative, are very important to produce beautiful works. The intrinsic and extrinsic elements of literary works are studied in this research. Intrinsic elements include theme, plot, characters, and setting, while extrinsic elements include social, cultural, and author biographical factors. The study shows that the appeal of literary works is influenced by the diction and majas chosen. Short stories have an aesthetic and emotional effect on readers due to their language style, which makes them a good medium for conveying moral messages and creative ideas.